ChemInform Abstract: Chemical Reactivity and Long‐Range Transport Potential of Polycyclic Aromatic Hydrocarbons. A review. Issue 6 (11th February 2014) - Keyte, Ian J.; Harrison, Roy M.; Lammel, Gerhard
Abstract Review: 472 refs.